Chronic bisphenol A exposure alters behaviors of zebrafish (Danio rerio). (November 2015) - Wang, Ju; Wang, Xia; Xiong, Can; Liu, Jian; Hu, Bing; Zheng, Lei
Abstract: The adult zebrafish ( Danio rerio ) were exposed to treated-effluent concentration of bisphenol A (BPA) or 17β-estradiol (E2) for 6 months to evaluate their effects on behavioral characteristics: motor behavior, aggression, group preference, novel tank test and light/dark preference. E2 exposure evidently dampened fish locomotor activity, while BPA exposure had no marked effect. Interestingly, BPA-exposed fish reduced their aggressive behavior compared with control or E2. Both BPA and E2 exposure induced a significant decrease in group preference, as well as a weaker adaptability to new environment, exhibiting lower latency to reach the top, more entries to the top, longer time spent in the top, fewer frequent freezing, and fewer erratic movements. Furthermore, the circadian rhythmicity of light/dark preference was altered by either BPA or E2 exposure. Our results suggest that chronic exposure of treated-effluent concentration BPA or E2 induced various behavioral anomalies in adult fish and enhanced ecological risk to wildlife. Highlights: BPA exposure induces various adult behavioral anomalies. BPA exposure decreases social interaction and environmental adaptation of zebrafish. BPA exposure increases ecological risk to wildlife. Abstract : Chronic bisphenol A exposure alters zebrafish behaviors.